Sugar content improvement by sonication in the pretreatment of empty fruit bunch hydrolysis - Rosalina Rosalina; Dwi Kemala Putri; Reni Sutri (Chemical Engineering Department, Faculty of Engineering, Universitas Sriwijaya in collaboration with Asosiasi Pendidikan Tinggi Teknik Kimia Indonesia (APTEKIM), 2024)
The empty palm fruit bunches (EFB) has great potential as an alternative feedstock for bioethanol production due to its high content of cellulose and hemicellulose. However, besides cellulose and hemicellulose, EFB also contains lignin, which can hinder the hydrolysis process and therefore requires delignification. This study aims to determine the effect of sonication in alkali delignification on the sugar content of hydrolysis. Ultrasonic in 37 KHz was performed at a temperature of 80 °C. Sonication process durations ranged from 30 minutes to 150 minutes using a 10 % (w/v) NaOH solvent. The hydrolysis of EFB fibers was carried out in a water bath at 80 °C using a 0.5 N sulfuric acid solvent in a ratio of 1:20 (w/v) for 2 hours. The sugar content was measured using the phenol-sulfuric acid method with UV-Visible spectrophotometry. In this study found that the ultrasonic irradiation time length gave good results at a time limit not exceeding 90 minutes due to hemicellulose characteristics . The highest sugar content was obtained at a sonication duration of 90 minutes, measuring 20.60 mg/L, which was 38.5 % higher than alkali delignification without sonication for 150 minutes. SEM analysis indicated that EFB had undergone changes in the surface morphology and structure. Qualitative FTIR analysis showed that the hydrolysis solution contained glucose and pentose, which are products of hydrolyzed cellulose and hemicellulose.